Front Cover: New Architectures for Designed Catalysts: Selective Oxidation using AgAu Nanoparticles on Colloid‐Templated Silica (Chem. Eur. J. 8/2018). Issue 8 (28th November 2017) - Shirman, Tanya; Lattimer, Judith; Luneau, Mathilde; Shirman, Elijah; Reece, Christian; Aizenberg, Michael; Madix, Robert J.; Aizenberg, Joanna; Friend, Cynthia M.
Abstract : A methodology for the formation of supported nanoparticle catalysts is demonstrated based on colloid‐templated porous silica embedded with AgAu bimetallic nanoparticles. These catalysts were utilized for a number of selective oxidation reactions and demonstrated high conversion efficiency, selectivity, stability, and reproducibility. The excellent catalytic performance stems from the ability to control size, composition, and positioning of the nanoparticles, and the porosity and interconnectivity of the substrate in one system. The modularity of the synthesis establishes a platform for making and testing rationally designed catalysts. More information can be found in the Full Paper by J. Aizenberg, C. M. Friend et al. onpage 1833 .